Pemanfaatan Biji Mangga Arum Manis (Mangifera indica L.) Sebagai Media Alternatif Pertumbuhan Candida albicans dan Aspergillus sp - S Sundari; W Wisrakarmila; F Faizah; Dest Marlina (Jurnal Pengelolaan Laboratorium Pendidikan, 2021)
Non-synthetic media is an alternative medium that utilizes ingredients found in nature. The chemical content of these ingredients is not known in detail but can be used because they are abundant in nature, easy to prepare and inexpensive. Several research results used alternative media from natural ingredients such as cassava starch for the growth of Aspergillus niger and Fusarium oxysporum , cowpeas, green beans, black soybeans, and soybean, ganyong, gembili and arrowroot , cereals, and beans . Purpose This study was to determine the seeds of mango arum sweth (Mangifera indica L.) can be used as an alternative growth medium for Candida albicans and Aspergillus sp. This research was conducted using an in vitro laboratory experimental method. The results showed that the medium mango seed (Mangifera indica L.) which had an average number of Candida albicans colonies was 1.12 x 106 cfu / ml while the medium mango seed arum sweet (Mangifera indica L.) in 72 hours incubation, the best diameter was obtained, namely 35 mm So it can be concluded that mango seed media (Mangifera indica L.) can be used as an alternative growth medium for Candida albicans and Aspergillus sp.